Formation of thin layer graphite wrapped meso-porous SiOx and its lithium storage application. Issue 18 (15th December 2019) - Liu, Dan; Fang, Kan; You, Xinhua; Tang, Haolin; Xie, Zhi-zhong; Li, Junsheng; Li, Xi; Qu, Deyu
Abstract: Here a nonstoichiometric silicon oxide with mesoporous structure and graphitized carbon coating layer was synthesized through a two-step process. A partially magnesiothermic reduction of mesoporous SiO2 precursor, followed by the pyrolysis of the generated mesoporous SiOx hybrid with various metal phthalocyanines was applied. The obtained mesoporous SiOx@graphite-M (M = Fe, Co and Ni) materials demonstrated a reversible capacity of 757, 721 and 628 mAh g −1 under the current density of 0.2 A g −1, respectively, as the anode materials in LIBs. They also exhibited superior rate performance, which can still maintain specific capacities of 588, 480 and 417 mAh g −1 even at current density of 5 A g −1 . When the mesoporous SiOx@graphite-Fe material is assembled with the LiFePO4 cathode to construct a full LIB, a capacity of 126 mAh g −1 with a retention rate over 99.2% after 100 cycles at a 1 C rate was presented. The good electrochemical performances of those SiOx based materials can be attributed to the transition metal induced graphitized carbon coating and the mesoporous structure, which not only offered the buffer media, but also provided enhanced electronic and ionic conductivity.